The Effectiveness of Local Government Internal Supervision in Preventing Corruption - Irvan Dhani Prabowo (PT Publikasiku Academic Solution, 2024)
Corruption at the local government level has become a serious concern in clean and accountable governance. Internal control is considered one of the main instruments in preventing corruption at the local government level. This study aims to evaluate the effectiveness of local government internal control in preventing corruption. The research method used is a qualitative approach with data collection through a literature study related to the topic discussed. The research findings show that internal control has become an important part of the local government structure and is influenced by various factors in achieving its effectiveness such as leadership style, organizational commitment, human resources, independence and autonomy, organizational culture, information technology, policies, and cooperation with external parties. The implications of this research highlight the need for improvements in the internal control system in local government to increase its effectiveness in preventing corruption. Recommendations are given to strengthen the independence of internal oversight institutions, improve human resource capacity, and increase transparency in the oversight process. This research is expected to make a significant contribution to further discussions on corruption prevention efforts at the local government level and the development of best practices in internal control